Rhinophyma: Combined Surgical Treatment and Quality of Life - Daoud, Mahmoud; Ullas, Gautham; Kumar, Rakesh; Raghavan, Ullas (Facial Plastic Surgery, 2020)
Rhinophyma is a progressive and disfiguring thickening of the nasal skin. It is typically found in middle-aged or elderly Caucasian males. The exact cause of the disease is unknown. There is excessive formation of scar-like tissue and hyperplasia of the sebaceous glands. This article will demonstrate our experience of treating rhinophyma using a combined surgical approach and propose a novel classification system. This is a retrospective analysis of cases operated by a single surgeon over 9 years using the Glasgow Benefit Inventory (GBI) tool. Thirty-three patients were identified. Twenty-nine patients had three techniques used in one sitting, two patients had two techniques used, and two further patients had one technique used. Total GBI showed a +50.99 result following surgery. Rhinophyma treatments can benefit patients as demonstrated by the GBI outcome. This can improve the patients' quality of life. The use of more than one technique in the same sitting potentially improves the outcome. Our classification system helps categorize the disease better as well as choosing the treatment and comparing disease and treatment. The Level of Evidence for the study is 4.
Keywords: rhinophyma; laser; quality of life; GBI